2018
DOI: 10.1177/2374373518805098
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of Care: Perspectives of Uninsured Free Clinic Patients

Abstract: Background:Continuity of care is vital to the success of a health-care system because it improves patient satisfaction and health outcomes, and reduces hospitalizations and emergency room visits.Objective:The purpose of this study was to examine free clinic patients’ perspectives of continuity of care in the United States.Method:A convenience sample of free clinic patients who were the age of 18 or older and spoke English or Spanish participated in a self-administered survey from January to April in 2017 (N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…This finding is consistent with findings in Canada 34 and the United States. 35 We also found that research has shown that patients with dyslipidemia, diabetes mellitus, hypertension, and asthma had better CoC scores than those with other chronic diseases. This is consistent with previous studies.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This finding is consistent with findings in Canada 34 and the United States. 35 We also found that research has shown that patients with dyslipidemia, diabetes mellitus, hypertension, and asthma had better CoC scores than those with other chronic diseases. This is consistent with previous studies.…”
Section: Discussionsupporting
confidence: 56%
“…6,44 Furthermore, they may experience lower care satisfaction and treatment plan adherence. 45 These findings may have implications for healthcare professionals and those who establish performance indicators to improve the CoC of patients with chronic diseases. Patients are often seen in multiple clinics and hospitals and prescriptions and medical records are not always shared among institutions.…”
Section: Discussionmentioning
confidence: 99%
“…It is important for clinicians to understand the social contextual issues, which include lack of awareness, accessibility, and acceptability of telehealth, in order to identify barriers to continuity of care. 91 The conversion to telemedicine demonstrates its utility as an effective tool for social distancing in clinical or other settings. 92 It may further marginalize others, however, who instead require physical distancing with social connectedness.…”
Section: Findings In Contextmentioning
confidence: 99%
“…Continuity of care is an important aspect of health care. A previous study at the free clinic has shown that clear guidelines and instruction from health care providers for a patient's treatment regimen was associated with an improved level of continuity of care (34). Improving continuity of care with patients with chronic conditions may result in higher medication adherence (35).…”
Section: Discussionmentioning
confidence: 99%